Bread, dignity and social justice: Populism in the Arab world. (May 2018) - Anderson, Lisa
Although they produced vastly more turmoil, the uprisings in the Arab world shared many characteristics with other early 21st-century popular protests on both the left and the right, from Spain's Indignados and Occupy Wall Street to the anti-elite votes for Brexit and Trump. The conviction that political elites and the states they rule, which were once responsible for welfare and development, now ignore and demean the interests and concerns of ordinary citizens takes many forms, but is virtually universal. The Arab world was only one site of this discontent, but the story of the Arab Spring insurrections provides a cautionary illustration of the perils in abdication of political authority and accountability and provokes questions about how we understand historical moments when passions outstrip interests.